Hippocampal and prefrontal processing of network topology to simulate the future - Javadi, Amir-Homayoun; Emo, Beatrix; Howard, Lorelei R.; Zisch, Fiona E.; Yu, Yichao; Knight, Rebecca; Pinelo Silva, Joao; Spiers, Hugo J. (Nature communications, 2017)
Topological networks lie at the heart of our cities and social milieu. However, it remains unclear how and when the brain processes topological structures to guide future behaviour during everyday life. Using fMRI in humans and a simulation of London (UK), here we show that, specifically when new streets are entered during navigation of the city, right posterior hippocampal activity indexes the change in the number of local topological connections available for future travel and right anterior hippocampal activity reflects global properties of the street entered. When forced detours require re-planning of the route to the goal, bilateral inferior lateral prefrontal activity scales with the planning demands of a breadth-first search of future paths. These results help shape models of how hippocampal and prefrontal regions support navigation, planning and future simulation. The hippocampus is known to support navigation, but how it processes possible paths to aid navigation is unknown. Here Javadi et al . show that entering streets drives hippocampal activity corresponding to the number of future paths, and that prefrontal activity corresponds to path-planning demands.